2022
DOI: 10.1002/cssc.202200752
|View full text |Cite
|
Sign up to set email alerts
|

Modulating p‐Orbital of Bismuth Nanosheet by Nickel Doping for Electrocatalytic Carbon Dioxide Reduction Reaction

Abstract: Electrochemical reduction of CO2 (CO2RR) to value‐added chemicals is an effective way to harvest renewable energy and utilize carbon dioxide. However, the electrocatalysts for CO2RR suffer from insufficient activity and selectivity due to the limitation of CO2 activation. In this work, a Ni‐doped Bi nanosheet (Ni@Bi‐NS) electrocatalyst is synthesized for the electrochemical reduction of CO2 to HCOOH. Physicochemical characterization methods are extensively used to investigate the composition and structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…85-1329), which is probably due to the amorphous nature or low Ti content (Figure 2a). [30] The averaged thickness of the Ti-Bi NSs measured by atomic force microscopy (AFM) is ≈1.7 nm (Figure 1i,j), which is only three to four atomic layers thick, demonstrating the ultrathin characteristic of the Ti-Bi NSs. [31] To investigate the effect of Ti doping on the catalytic performance of Bi NSs, pure Bi NSs with similar morphology to Ti-Bi NSs were synthesized via long-term reduction of Bi 4 Ti 3 O 12 precursor at an ultra-low potential.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…85-1329), which is probably due to the amorphous nature or low Ti content (Figure 2a). [30] The averaged thickness of the Ti-Bi NSs measured by atomic force microscopy (AFM) is ≈1.7 nm (Figure 1i,j), which is only three to four atomic layers thick, demonstrating the ultrathin characteristic of the Ti-Bi NSs. [31] To investigate the effect of Ti doping on the catalytic performance of Bi NSs, pure Bi NSs with similar morphology to Ti-Bi NSs were synthesized via long-term reduction of Bi 4 Ti 3 O 12 precursor at an ultra-low potential.…”
Section: Resultsmentioning
confidence: 98%
“…85–1329), which is probably due to the amorphous nature or low Ti content ( Figure a). [ 30 ] The averaged thickness of the TiBi NSs measured by atomic force microscopy (AFM) is ≈1.7 nm (Figure 1i,j), which is only three to four atomic layers thick, demonstrating the ultrathin characteristic of the TiBi NSs. [ 31 ]…”
Section: Resultsmentioning
confidence: 99%
“…Zn-doped Bi nanosheets were prepared by referencing the previous literature reports. 26 First, Bi(NO 3 ) 3 ·5H 2 O (0.95 mmol), Zn(NO 3 ) 2 ·6H 2 O (0.05 mmol), and CHNaO 2 (0.05 mmol) were dissolved in a mixed solvent of 20 mL DMF and 2 mL DI water using ultrasonic dissolution and stirring for 45 min. The mixture obtained was transferred to a Teflon-lined autoclave.…”
Section: Methodsmentioning
confidence: 99%
“…11,19 Recently, a considerable number of research studies have reported that doping of heteroatoms is conductive to enhancing the intrinsic catalytic activity of electrocatalysts, which can induce charge redistribution in the pristine material, thus optimizing the adsorption behavior of specific intermediates and improving the CO 2 RR kinetics. 20–22 The overpotential of the CO 2 RR can be effectively reduced by doping with B, 23 Te, 24 Ti, 25 or Ni, 26 and the faradaic efficiency of formate can reach a high level, but there does not seem to be much concern in terms of stability. Recent studies have shown that the deactivation of Bi-based catalysts may be related to the partial remodeling of metal Bi into Bi 2 O 2 CO 3 , and that metal doping can modify the reconstruction behavior of metal Bi.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides an effective strategy for developing active and selective CO2RR electrocatalysts by modulating electron density states. [7] Kaifan Liu, Zongjun Li et al studied the controlled synthesis of two kinds of gold nanoclusters, Au24NCs and Au25NCs, and studied their catalytic activity on CO2RR. The results showed that Au24NCs /C had higher catalytic activity on CO2RR.…”
Section: Introductionmentioning
confidence: 99%